Field evaluation: Performance of Panel BO-1 of tissue cultured RRIM 2025, RRIM 600 and GL 1 trees - Nor Mayati, C.H.; Ahmad Shukri, H., Abd Razak, A. (Proceedings of the IRRDB International Rubber Conference 2023, 20-21 February 2023, IRRDB, Kuala Lumpur, Malaysia, pp. 28-36.)
Tapping commenced at 12 years after planting and yield performance including monthly and annual yield, tree performance, g/t/t, and dry rubber content (DRC) were evaluated. Physical stresses of the tapped trees were evaluated by monitoring bark dryness on the final of the fourth-year study period. Growth and development of the available trees was monitored annually and increment in bole volume, tree height, and girth measured in four consecutive years were also recorded. RRIM 2025 V1 (first vegetative generation) consistently recorded the highest g/t/t throughout the trial as compared to their mother plant, RRIM 2025MP, and other test and control trees, equally high g/t/t was recorded for RRIM 2025NB (normal budding-control). On the other hand, the DRC was significantly higher for RRIM 2025 MP as compared to other test and control trees. The data gathered has identified 15 trees as high performers that were able to produce over 100 g/t/t of latex. Average g/t/t for the four years trial was employed to shortlist five promising latex producers i.e. C18 (RRIM 2025NB) at an average of 158 g/t/t, C8 (RRIM 2025NB) at 141 g/t/t, EAC 106/10 (RRIM 2025V1) at 158 g/t/t, EAC 33/2 (RRIM 2025 V1) at 159 g/t/t, and EAC 36 (RRIM 600MP) at 135 g/t/t. These trees could be propagated to produce high latex yielding clones. Tree dryness generally increased with time and was significantly high (P< 0.0001) throughout all three yielding periods in the final year of the trial. When tested among clones, only RRIM 600V1 and GL 1MP showed significantly lower incidence of dryness at 44% and 51% respectively. RRIM 2025 MP and V1 succumbed to severe dryness at >70%. However, RRIM 2025 MP performed better in terms of growth rate as compared to the other test and control trees.
Keywords: Dryness; Growth rates; Latex; Tissue culture